Safety Challenges for Autonomous Vehicles in the Absence of Connectivity - Spandana Sagam (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the critical safety challenges faced by autonomous vehicles (AVs) operating in environments without connectivity. As the global AV market expands rapidly, the disparity in Vehicle-to-Everything (V2X) infrastructure implementation across regions necessitates AVs to function safely in both connected and non-connected scenarios. The article explores five key areas of concern: limited real-time information access, absence of cooperative driving capabilities, lack of remote software updates, reduced traffic ecosystem support, and increased vulnerability to cybersecurity threats. By analyzing data from various transportation studies and industry reports, the article highlights the significant impact of these challenges on AV performance, efficiency, and safety. The research underscores the importance of developing robust, adaptable systems that can operate effectively in diverse connectivity environments, emphasizing the need for advanced onboard sensors, sophisticated AI algorithms, and enhanced traffic management strategies to mitigate the risks associated with non-connected autonomous driving.